Drexel dragonThe Math ForumDonate to the Math Forum

Ask Dr. Math - Questions and Answers from our Archives
_____________________________________________
Associated Topics || Dr. Math Home || Search Dr. Math
_____________________________________________

Plus or Minus Sign


Date: 03/08/2002 at 17:59:07
From: Kim
Subject: Algebra 1 (equations)

What does this equation mean: y = + k 
                                  -

The - sign is directly under the + sign.


Date: 03/09/2002 at 12:54:31
From: Doctor Ian
Subject: Re: Algebra 1 (equations)

Hi Kim,

This is really shorthand for two separate equations:

  y = k
  y = -k

It's a little like when you say 'Pat is at either McDonalds or Burger 
King'. You know he's at one of those places, but you don't know which.

Why would we need to express this with numbers?  Here is an example.  
The equation 

  y = x^2

describes a parabola. If we choose a value of x, we can compute the 
corresponding value of y:

  x=2   y=2^2 =  4
  x=3   y=3^3 =  9
  x=4   y=4^2 = 16

But note that for any given value of y, there are _two_ values of x 
that give rise to it:

  x=2   y=2^2    = 4
  x=-2  y=(-2)^2 = 4

  x=3   y=3^2    = 9
  x=-3  y=(-3)^2 = 9
 
So what if we want to go the other way? What if we have a value for y, 
and we want to know what the corresponding value of x would be?  Well, 
there are two values:

  y=4   x=sqrt(y) = either 2 or -2
  y=9   x=sqrt(y) = either 3 or -3

and so on. In this case, we use the shorthand '+/-' ('plus or minus') 
to indicate the ambiguity:

  y=4   x=sqrt(y) = +/- 2
  y=9   x=sqrt(y) = +/- 3

In lots of cases, we can simply ignore the negative value. But 
ignoring it is different from not realizing that it exists. Forgetting 
about it completely is the basis of many so-called 'false proofs', 
like this one:

  [1]           -2 = -2

  [2]        4 - 6 = 1 - 3

  [3]  4 - 6 + 9/4 = 1 - 3 + 9/4

  [4]  (2 - 3/2)^2 = (1 - 3/2)^2                

  [5]      2 - 3/2 = 1 - 3/2            
                                   
  [6]            2 = 1

Do you see the problem? There are really four possible versions of 
step [5]:

  [5a]     2 - 3/2 = 1 - 3/2            False.

  [5b]  -(2 - 3/2) = 1 - 3/2            True.

  [5c]     2 - 3/2 = -(1 - 3/2)         True.   

  [5d]  -(2 - 3/2) = -(1 - 3/2)         False.  

This could be written more simply as

  [5d]  +/-(2 - 3/2) = +/-(1 - 3/2)         

But this would rule out the final step that makes the proof 'work'.

I hope this helps. Write back if you'd like to talk more about this, 
or anything else. 

- Doctor Ian, The Math Forum
  http://mathforum.org/dr.math/   
    
Associated Topics:
High School Basic Algebra
High School Linear Equations
Middle School Algebra
Middle School Equations

Search the Dr. Math Library:


Find items containing (put spaces between keywords):
 
Click only once for faster results:

[ Choose "whole words" when searching for a word like age.]

all keywords, in any order at least one, that exact phrase
parts of words whole words

Submit your own question to Dr. Math

[Privacy Policy] [Terms of Use]

_____________________________________
Math Forum Home || Math Library || Quick Reference || Math Forum Search
_____________________________________

Ask Dr. MathTM
© 1994-2013 The Math Forum
http://mathforum.org/dr.math/